Intraductal ultrasonography for biliary strictures - Young Koog Cheon (Korean Society of Gastrointestinal Endoscopy, 2023)
When diagnosing the nature of biliary strictures, it is sometimes difficult to perform non-invasive methods such as ultrasound, spiral computed imaging, magnetic resonance imaging, or endoscopic ultrasonography. Thus, treatment decisions are usually based on biopsy results. However, brush cytology or biopsy, which is widely used for biliary stenosis, has limitations owing to its low sensitivity and negative predictive value for malignancy. Currently, the most accurate method is bile duct tissue biopsy under direct cholangioscopy. On the other hand, intraductal ultrasonography administered under the guidance of a guidewire has the advantages of easy administration and being less invasive, allowing for adequate examination of the biliary tract and surrounding organs. This review discusses the usefulness and drawbacks of intraductal ultrasonography for biliary strictures.